Financial aspects of sustainable use of bioresources by fisheries enterprise - Drahan, Oksana; Драган, Оксана; Prysiazhniuk, Nataliia; Присяжнюк, Наталія; Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; Gorchanok, A. V.; Горчанок, Анна Володимирівна (Дніпровський ДАЕУ, 2022)
The article is devoted to the economic essence of the concept of "sustainable use of biological resources". An analysis of the prospects for the development of the domestic fish market was made. It has been proven that the further development of the fish market should be based on the creation of an effective organizational and economic mechanism, its functioning, state stimulation of the development of the market infrastructure, strengthening of quality control of fish and fish products, modernization of fishing enterprises, updating of the material and technical base and increasing the capitalization of the enterprise. Стаття присвячена економічній сутності поняття «збалансоване використання біоресурсів». Проведено аналіз перспектив розвитку вітчизняного рибного ринку. Доведено, що подальший розвиток рибного ринку має базуватися на створенні ефективного організаційно-економічного механізму його функціонування, державному стимулюванні розвитку ринкової інфраструктури, посиленні контролю якості риби та рибної продукції, модернізації рибогосподарських підприємств, оновлення матеріально-технічної бази та підвищення капіталізації підприємства.
Фінансові аспекти сталого використання біоресурсів рибогосподарськими підприємствами
Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477
Keywords: enterprises; підприємства; market; ринок; fish; риба; aquatic biological resources; водні біоресурси; financial resources; фінансові ресурси